Efeito da fibra nas perdas endógenas e balanço de nitrogênio de suínos em crecimento - Rocha, Leonardo Tombesi da (2016)
The first part of the dissertation describes a meta-analytic study in order to quantify the influence of fiber on endogenous losses of nitrogen (N) and amino acids (AA), and identify ways of expression of fiber that better explain the effect of this component on these losses. The second part covers two digestibility experiments designed to determine whether fibrous feedstuffs may contribute to the N balance of pigs. About the meta-analysis, from the regression analysis of total endogenous N (NENDTOTAL) (mg/kg dry matter intake (DMI)) and the concentrations of total dietary fiber (TDF) and neutral detergent fiber (NDF), resulted the equations: y= 1504 + 160.8 * TDF (r2= 0,73) and y= 1773 + 161.0 * NDF (r2= 0,69). The slopes of the regression between NENDTOTAL and TDF or NDF indicated that by every percentage point increase in dietary fiber the NENDTOTAL is increased by 160 mg/kg DMI. The specific endogenous losses of N (NENDSPEC) was used as dependent variable in relation with TDF and NDF. The result was described by the equations: y= 124 + 154.9 * TDF (r2= 0,69) and y= 210 + 146.9 * NDF (r2= 0,60). We can observe by the slope of regression between NENDSPEC and TDF or NDF is an increase of 150 mg/kg DMI in NENDSPEC by each percentage point increase in dietary fiber. About AA, it was observed that the fiber influences more intensively the specific endogenous losses of threonine and valine than other AA. We conclude that it is possible to assume that the endogenous losses of N and AA are directly proportional to the fiber intake and the TDF and NDF were the variables that better describe this relation. For the digestibility experiment, 24 pigs were divided in experimental two groups: a) CT1 control diet, and b) WB diet with inclusion of 15% wheat bran, in the trial 1 and, c) CT2 control diet, and d) SH diet with inclusion of 6% of soybean hulls, in the trial 2. The NRET was higher (15%) in the pigs ingesting WB diet, although the proportion of NRET expressed relative to ingested N (NING) (50%) or absorbed N (NABS) (55.5%) was similar (P>0.05) between treatments. The inclusion of SH had no effect (P>0.05) in NRET when the result was expressed in absolute (g/d) or proportional terms. On average, the NRET represented 48 and 55.5% of NING and NABS for CT2 and SH diets, respectively. Looking all data, we can observe that the WB increased NRET and that increase it was proportional to NABS. On the other hand, the amount of N incorporated with the SH was totally recovered in the feces, indicating a low digestibility of this ingredient. The NABS utilization efficiency was not affected by the inclusion of fibrous feedstuffs, which indicates that in the studied levels, adding WB or SH, does not significantly impacts in the post-absorptive metabolism of N, counteracting our initial hypothesis.